2020
DOI: 10.21037/tcr-20-2441
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative radiotherapy versus whole‑breast external beam radiotherapy, and other factors associated with the prognosis of early breast cancer treated with breast-conserving surgery and radiotherapy: a retrospective study from SEER database

Abstract: Background: This study was aimed to investigate the prognostic factors of early breast cancer treated with breast-conserving surgery (BCS) and radiotherapy. Besides, we focused our attention exclusively on the comparison of the impact on prognosis between intraoperative radiotherapy (IORT) and whole-breast external beam radiotherapy (EBRT).Methods: An observational cohort study was performed on patients with Tis-2 N0-1 M0 breast cancer from the Surveillance, Epidemiology, and End Results (SEER) database who tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
0
0
1
Order By: Relevance
“…Our study found no statistically significant difference in recurrence‐free survival and overall survival rates between two groups of patients who received either IORT or EBRT 39–41 . These findings are consistent with a substantial body of previous research, including a meta‐analysis by Wang et al, which also failed to demonstrate a meaningful difference between the two treatment modalities in terms of recurrence‐free survival and overall survival.…”
Section: Discussionsupporting
confidence: 91%
“…Our study found no statistically significant difference in recurrence‐free survival and overall survival rates between two groups of patients who received either IORT or EBRT 39–41 . These findings are consistent with a substantial body of previous research, including a meta‐analysis by Wang et al, which also failed to demonstrate a meaningful difference between the two treatment modalities in terms of recurrence‐free survival and overall survival.…”
Section: Discussionsupporting
confidence: 91%
“…Значительным недостатком ДЛТ является большая продолжительность лечения. Для облучения молочной железы в дозе 45-50 Гр, необходимо провести до 25 фракций, на протяжении 3-5 нед [19]. Тогда как концепция ИОЛТ способствует существенному сокращению курса лучевой терапии до 1 сеанса, продолжительностью 15-40 мин, в зависимости от выбранного аппликатора, уменьшению объема облучаемой ткани и улучшению косметического эффекта операции [20][21][22].…”
Section: Discussionunclassified